ANALISIS PENGARUH KESADARAN PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN PPH FINAL PADA UMKM KULINER DI KOTA PADANG - Lisa Gustiani; Tartila Devy (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study investigates the effect of tax awareness and tax sanctions on the compliance of Final Income Tax (PPh Final) among Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector of Padang City, Indonesia. A quantitative associative approach was employed, surveying 36 purposively selected respondents. Data were gathered through validated and reliable structured questionnaires and analysed using multiple linear regression (SPSS 25). The results reveal that both tax awareness and tax sanctions exert a positive and significant influence—individually and jointly—on MSME compliance with Final Income Tax obligations. These findings highlight the critical role of enhanced tax literacy and consistent enforcement of sanctions in improving tax compliance within the MSME sector. Practically, the Directorate-General of Taxes should design integrated educational programs and progressive sanction policies tailored to the characteristics of culinary MSMEs in regional contexts.